The Beauty Terms Used in True Beauty Webtoon: The Word Formation Analysis - Sa'adah, Firda Rofiatus (Journal of Literature, Linguistics, & Cultural Studies, 2023)
The researcher conducted an analysis of the word-formation of beauty-related terms used in Yaongyi's Webtoon "True Beauty." The primary objective was to identify the morphological processes involved in creating these beauty terms within the storyline. The study utilized qualitative methods, with the researcher as the main instrument, collecting data on various words and phrases related to beauty found throughout the Webtoon. In total, the researcher identified 62 beauty terms from the selected episodes and subsequently categorized them according to word-formation processes proposed by O'Grady (1997) and Yule (2010). Six main word-formation processes were identified: compounding, derivation, clipping, borrowing, conversion, and backformation. Among these, compounding was found to be the most prevalent method of word formation for beauty terms in the "True Beauty" Webtoon. The study revealed that compounding was the dominant process for forming beauty terms in the Webtoon "True Beauty," which differed from a previous investigation that focused on technology terms in other Webtoons and showed a prevalence of process affixes. These findings suggest that language styles can be influenced by specific subject fields. Furthermore, the researcher discovered several new terms not present in standard dictionaries like Oxford or Cambridge, highlighting the creative and innovative language use within the context of the Webtoon.